2020
DOI: 10.3389/fmolb.2020.00157
|View full text |Cite
|
Sign up to set email alerts
|

Immune Phenotyping Based on the Neutrophil-to-Lymphocyte Ratio and IgG Level Predicts Disease Severity and Outcome for Patients With COVID-19

Abstract: Introduction: A recently emerging respiratory disease named coronavirus disease 2019 (COVID-19) has quickly spread across the world. This disease is initiated by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and uncontrolled cytokine storm, but it remains unknown as to whether a robust antibody response is related to clinical deterioration and poor outcome in COVID-19 patients. Methods: Anti-SARS-CoV-2 IgG and IgM antibodies were determined by chemiluminescence analysis (CLIA) in COVID-19 patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
335
2
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(392 citation statements)
references
References 19 publications
31
335
2
13
Order By: Relevance
“…Accordingly, it would be necessary to study each of the present clinical clusters genetically and to verify that each cluster has a differentiated genetic background. In the literature, some studies attempted to phenotype patients with COVID-19 as a function of the immune response, and others is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint The copyright holder for this this version posted September 15, 2020. ; https://doi.org/10.1101/2020.09.14.20193995 doi: medRxiv preprint suggested phenotyping as a function of pathophysiology [16,17]. It would be interesting to combine all methods of phenotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it would be necessary to study each of the present clinical clusters genetically and to verify that each cluster has a differentiated genetic background. In the literature, some studies attempted to phenotype patients with COVID-19 as a function of the immune response, and others is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint The copyright holder for this this version posted September 15, 2020. ; https://doi.org/10.1101/2020.09.14.20193995 doi: medRxiv preprint suggested phenotyping as a function of pathophysiology [16,17]. It would be interesting to combine all methods of phenotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin G (IgG) and immunoglobulin M (IgM) are known antibodies for monitoring humoral immune responses to infections by viruses such as SARS-CoV-2. [18][19][20][21][22][23][24] Because of their convenience and cost-efficiency, new serological assays of IgG and IgM antibodies have been recognised as a promising diagnostic tool to complement viral nucleic acid screening in the atrisk populations. 25 Of note, IgG/IgM seroconversion can be observed in many patients after their infections with SARS-CoV-2, 4,18,20,23,26 and serological responses are associated with disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…25 Of note, IgG/IgM seroconversion can be observed in many patients after their infections with SARS-CoV-2, 4,18,20,23,26 and serological responses are associated with disease severity. 19 For instance, an observational study of 32 critically ill and 141 noncritically ill patients reported IgM and IgG seroconversion rates of 82.7% and 64.7%, respectively. 18 Furthermore, IgG/IgM seroconversion could be detected along with a steady decline in viral loads in mildly ill patients, 4 though IgG seroconversion can be observed at the same time or earlier than IgM seroconversion in symptomatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory parameters such as neutrophil-to-lymphocyte ratio (2,3), C-reactive protein (CRP), interleukin (IL)-6 and dimer-D levels (4) are reported as indicators of COVID-19 severity when associated to clinical features of the infection. COVID-19 patients hospitalized at intensive care unit (ICU) exhibit augmented levels of inflammatory cytokines and infection biomarkers, such as interleukin (IL)-1B, IL-7, IL-8, IL-9, IL-10, interferon (IFN)-γ, interferon gamma-inducible protein (IP)-10, monocyte chemoattractant protein (MCP)-1, macrophage inflammatory protein (MIP)1A, MIP1B, platelet-derived growth factor (PDGF), tumor necrosis factor-alpha (TNFα), and vascular endothelial growth factor (VEGF).…”
Section: Introductionmentioning
confidence: 99%